Faktor-faktor yang mempengaruhi nilai perusahaan pada perusahaan non keuangan - DEWI LUSIANA; DEWI AGUSTINA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to get empirical evidence about factor- factor which affect to firm value on non-financial companies. This research was conducted to determine the effect of managerial ownership, financial leverage, profitability, firm size, investment opportunity, dividend policy, intangible asset, liquidity ratio, and asset turnover to firm value. The samples in this research consist of 33 non-financial companies that have been listed in Indonesia Stock Exchanges (BEI) from period 2011 until 2014. Samples selected based on purposive sampling method with total 132 research data were used. The statistical used in this research was multiple regression method. The research showed that financial leverage, dividend policy, liquidity ratio, and asset turnover had no effect to firm value. Only managerial ownership, profitability, firm size, investment opportunity, and intangible asset had effect to firm value.